2013
DOI: 10.3390/molecules180910857
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Partial Characterization and Immobilization of a Mannose-Specific Lectin from Seeds of Dioclea lasiophylla Mart.

Abstract: Abstract:Lectin from the seeds of Dioclea lasiophylla (DlyL) was purified in a single step by affinity chromatography on a Sephadex ® G-50 column. DlyL strongly agglutinated rabbit erythrocytes and was inhibited by monosaccharides ( D -mannose and α-methyl-Dmannoside) and glycoproteins (ovalbumin and fetuin). Similar to other Diocleinae lectins, DlyL has three chains, α, β and γ, with mass of 25,569 ± 2, 12,998 ± 1 and OPEN ACCESSMolecules 2013, 18 10858 12,588 ± 1 Da, respectively, and has no disulfide bonds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…The Artemia lethality test has been used successfully to determine the toxicity of bioactive compounds that have a variety of pharmacological activities, including anticancer agents, antivirals, insecticides, pesticides, and anti‐HIV compounds (Carballo et al ., ; Pervin et al ., ; Ho et al ., ). Other studies evaluated the toxic effect of some ConA‐like lectins, and they reported LC 50 values ranging from 45.85 to 376.48 µg/ml (Pinto‐Junior et al ., ; Arruda et al ., ). In comparison with similar lectins, DrfL exhibited low toxicity against Artemia sp.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The Artemia lethality test has been used successfully to determine the toxicity of bioactive compounds that have a variety of pharmacological activities, including anticancer agents, antivirals, insecticides, pesticides, and anti‐HIV compounds (Carballo et al ., ; Pervin et al ., ; Ho et al ., ). Other studies evaluated the toxic effect of some ConA‐like lectins, and they reported LC 50 values ranging from 45.85 to 376.48 µg/ml (Pinto‐Junior et al ., ; Arruda et al ., ). In comparison with similar lectins, DrfL exhibited low toxicity against Artemia sp.…”
Section: Resultsmentioning
confidence: 97%
“…The agglutination of DrfL was inhibited by α ‐methyl‐ d ‐mannoside, d ‐mannose, and d ‐glucose (Table ). This specificity is similar to that of other lectins in the Dioclea genus (Nascimento et al ., ; Pinto‐Junior et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The lectin from Dioclea lasiophylla seeds is another example of lectins presenting bands of different molecular weights. DlyL is composed of three different chains with different molecular weights and no bisulfide bonds present (Pinto-Júnior et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A lectin from Curcuma amarissima rhizomes showed in vitro antiproliferative activity against a breast cancer cell line (BT 474) with an LC 50 value of approximately 21.1 μg (Kheeree et al, 2010). Highly toxic lectins were isolated from Abrus pulchellus and Mulberry seeds having LC 50 values of 3.5 mg/ml and 21.87 μg/ml whereas other lectins from the seeds of Dioclea lasiophylla and tubers of Nymphaea nouchali had much lower values like 45.85 and 120 μg/ml, respectively (Ramos et al, 1998;Absar et al, 2005;Pinto-Junior et al, 2013;Kabir et al, 2012). Presence of a non-toxic lectin from Sebastiania jacobinensis bark to Artemia nauplii is also reported (Vaz et al, 2010).…”
Section: Brine Shrimp Nauplii Lethality Assaymentioning
confidence: 99%